2021
DOI: 10.1111/cen.14628
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CYP11B1 and CYP11B2 in adrenal adenoma correlates with clinical characteristics of primary aldosteronism

Abstract: ObjectivePrimary aldosteronism (PA) shows histological heterogeneity and clinical variability, including the coexistence of hypercortisolemia. Immunohistochemical analyses of steroidogenic enzymes in adrenal tissues have provided new insights into the pathogenesis of PA. However, a comprehensive analysis of the association between enzyme expression and clinical characteristics of PA has rarely been conducted. We aimed to investigate the correlation between clinical characteristics and steroidogenic enzyme expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A study by Nakamura et al ( 38 ) demonstrated that CYP11B1, a steroidogenic enzyme, which converts deoxycorticosterone to corticosterone, was diffusely detected in the APA, and it could play a pivotal role in the tumor genesis. In another recent study, Ahn et al ( 39 ) showed lower CYP11B1 expression in adrenal adenomas of patients with PA compared with those affected by adrenal Cushing's syndrome. These findings underlined how the variable expression of steroidogenic enzymes in adrenal lesions is associated with the clinical heterogeneity of hormone overproduction.…”
Section: Discussionmentioning
confidence: 89%
“…A study by Nakamura et al ( 38 ) demonstrated that CYP11B1, a steroidogenic enzyme, which converts deoxycorticosterone to corticosterone, was diffusely detected in the APA, and it could play a pivotal role in the tumor genesis. In another recent study, Ahn et al ( 39 ) showed lower CYP11B1 expression in adrenal adenomas of patients with PA compared with those affected by adrenal Cushing's syndrome. These findings underlined how the variable expression of steroidogenic enzymes in adrenal lesions is associated with the clinical heterogeneity of hormone overproduction.…”
Section: Discussionmentioning
confidence: 89%
“…Cushing’s syndrome is caused either by excessive medication of cortisol-like compounds or by tumors, such as pituitary and adrenal adenomas, which express high levels of the cortisol synthase gene CYP11B1 and thereby produce a high level of cortisol [ 84 , 85 ]. Previous reports have demonstrated the overexpression of CYP11B1 in adrenal Cushing’s syndrome [ 86 ]. However, the molecular mechanism underlying the CYP11B1 overexpression in adrenal Cushing’s syndrome remains unclear.…”
Section: Epigenetic Control Of Cyp11b1mentioning
confidence: 99%
“…The IHC examination of CYP11B2 and CYP11B1, key enzymes in aldosterone and cortisol biosynthesis, in adrenal slices is commonly used to identify the source of aberrant secretions of aldosterone and cortisol ( 124 , 125 ). A recent study demonstrated that the immunoreactivity of CYP11B1 was higher in adrenal adenomas of PA patients with concurrent ACS compared to PA patients without ACS ( 126 ). Interestingly, some studies have reported that the immunoreactivity of CYP11B1 was higher in adenomas without KCNJ5 mutations compared with adenomas harboring mutant KCNJ5 ( 92 , 127 ).…”
Section: Kcnj5 Somatic Mutationsmentioning
confidence: 99%